Improving Water Sanitation and Hygiene (WASH) Services in Rural Punjab: A Policy Imperative for Public Health and Development (Journal of Social Sciences Review, 2025)
Access to safe water, adequate sanitation, and hygiene (WASH) is fundamental to public health, yet rural regions of Punjab continue to face persistent challenges in WASH service delivery. This study employs an interdisciplinary approach to examine the structural, behavioral, and institutional factors that contribute to WASH-related vulnerabilities in rural Punjab. Grounded in the Social Determinants of Health Framework, the Ecological Model of Health Behavior, and Governance and Policy Implementation Theory, the research explores how socio-economic disparities, community norms, and governance inefficiencies collectively impact health outcomes and the effectiveness of WASH interventions. Findings highlight that WASH inequities are closely linked to poverty, gender disparities, education levels, and institutional fragmentation. The study highlights the importance of developing integrated, equity-focused policies that extend beyond infrastructure provision to encompass behavior change strategies, strengthened local governance, and increased community participation. Ultimately, the research advocates for a holistic, multi-level policy response to improve WASH services as a public health and development imperative in rural Punjab.
Keywords: Public Health; Water; Sanitation and Hygiene (WASH); Challenges and Service Delivery of WASH; Collective Community Interventions; Policy Transformation